2020
DOI: 10.3389/fphys.2020.00866
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Plays a Critical Protective Role in Nicotine-Related Abdominal Aortic Aneurysm

Abstract: Smoking is a major risk factor for abdominal aortic aneurysm (AAA). Among the components of smoke, nicotine is known to exert pro-atherosclerotic, prothrombotic, and proangiogenic effects on vascular smooth muscle cells (VSMCs). The current study was designed to investigate the mechanisms through which nicotine induces vascular wall dysfunction and to examine whether melatonin protects against nicotine-related AAA. Methods: In this study, an enzyme-linked immunosorbent assay (ELISA) was used to measure melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In Ang II-infused mice, it was found that α7nAChR deficiency promoted inflammatory responses, accelerated the abdominal aortic dilation and displayed disruption of elastin. Consistent with the idea that VSMCs phenotype was transformed to synthetic phenotype during the development of AAA [ 29 ], it was found that activating α7nAChR significantly prevented the switch of VSMCs from contractile to synthetic phenotype in Ang II-infused ApoE −/− mice, while this switch was facilitated in α7nAChR −/− mice. However, duo to the limited amount of aged α7nAChR −/− mice, either the AAA incidence or maximal abdominal aortic diameter only displayed an increase with no statistical significance in Ang II-infused α7nAChR −/− mice when compared with the WT ones.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In Ang II-infused mice, it was found that α7nAChR deficiency promoted inflammatory responses, accelerated the abdominal aortic dilation and displayed disruption of elastin. Consistent with the idea that VSMCs phenotype was transformed to synthetic phenotype during the development of AAA [ 29 ], it was found that activating α7nAChR significantly prevented the switch of VSMCs from contractile to synthetic phenotype in Ang II-infused ApoE −/− mice, while this switch was facilitated in α7nAChR −/− mice. However, duo to the limited amount of aged α7nAChR −/− mice, either the AAA incidence or maximal abdominal aortic diameter only displayed an increase with no statistical significance in Ang II-infused α7nAChR −/− mice when compared with the WT ones.…”
Section: Discussionsupporting
confidence: 76%
“…Vascular smooth muscle cells (VSMCs) had an important effect on maintaining the integrity of aortic wall. It has been reported that the VSMCs phenotype could be transformed from a contractile phenotype to a synthetic phenotype in the pathophysiological process of AAA [ 29 ]. Thus, the expressions of α-SMA (a marker of contractile phenotype) and OPN (a marker of synthetic phenotype) were examined to determine the role of α7nAChR on VSMCs phenotype in AAA.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of the cargo protein P62 and autophagosomal structure protein Lc3B II induced by bafilomycin A1 indicated that resveratrol activated autophagy. The effects of bafilomycin A1 on P62 and Lc3B II in the regulation of autophagosome-lysosome fusion and degradation have been widely verified in some studies of melatonin resistance to abdominal aortic aneurysm and quercetin interference with osteosarcoma cells [ 59 , 60 ]. These results further support our hypothesis that resveratrol activates autophagy by regulating the protein and mRNA levels of autophagy-related genes, thereby protecting against H 2 O 2 -induced luteinized granulosa cell dysfunction in terms of enhancing cell viability, improving the secretion of progesterone and estradiol, and inhibiting apoptosis ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) signaling pathway plays a key role in the regulation of autophagy and apoptosis 12,13 . Accumulating evidence indicates that MT activates autophagy by inhibiting the mTOR pathway 14–16 ; it has also been shown to regulate mitophagy through the adenosine monophosphate‐activated protein kinase/mTOR pathway 17,18 . Moreover, studies have demonstrated that MT regulates autophagy‐related (ATG) proteins, such as Beclin‐1—a key factor in autophagy induction 14,19–21 .…”
Section: Introductionmentioning
confidence: 99%